2021
DOI: 10.3390/antibiotics10101264
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Profile of Actinomycin D Analogs Secreted by Egyptian Desert Streptomyces sp. DH7

Abstract: Egyptian deserts are an underexplored ecological niche, especially the Sinai Peninsula. In our recent study, we explored this extreme environment and shed light on the bioactive capabilities of desert Actinobacteria isolated from Sinai. Fifty desert Actinobacteria were isolated from the Sinai desert using mineral salt media, basal media, and starch casein media. The filtrate of Streptomyces sp. DH 7 displayed a high inhibitory effect against multidrug-resistant Staphylococcus aureus (MRSA) strains. The 16S rDN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…20,21 Streptomycetes belonging to the family Streptomycetaceae, are Gram-positive bacteria, which have a widespread distribution in nature and are found in soils, waters, as well as in plants as endophytes. 22 Actinomycins are a well-known class of chromopeptide isolated from many species of Streptomyces, and have been reported to exhibit anti-MRSA (methicillin-resistant Staphylococcus aureus), 23,24 antitumor, 25 and anti-tuberculosis 26 activities. Actinomycin consists of two macrocyclic pentapeptidolactones attached to an actinocinyl chromophore through amide bonds.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Streptomycetes belonging to the family Streptomycetaceae, are Gram-positive bacteria, which have a widespread distribution in nature and are found in soils, waters, as well as in plants as endophytes. 22 Actinomycins are a well-known class of chromopeptide isolated from many species of Streptomyces, and have been reported to exhibit anti-MRSA (methicillin-resistant Staphylococcus aureus), 23,24 antitumor, 25 and anti-tuberculosis 26 activities. Actinomycin consists of two macrocyclic pentapeptidolactones attached to an actinocinyl chromophore through amide bonds.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this study investigated the antibacterial activity of actinomycin D produced by strain LS-2, and the results showed that it had about 14 mm inhibition zone against both gram-positive bacteria and gram-negative bacteria. Amin et al (28) screened a Streptomyces from the desert of Egypt and characterized its antibacterial activity with multidrug-resistant Staphylococcus aureus. Moreover, the diameter of the bacteriostatic zone was 4 mm-22 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the above-mentioned results, the yellow pigment produced by strain LS-2 was identified as actinomycin D, and the structure is shown in Appendix 3 (28).…”
Section: The Chemical Structure Of the Pigmentmentioning
confidence: 99%
“…The strains of Streptomyces genus employ their secondary metabolites as weapons to inhibit phytopathogenic fungi ( Amin et al, 2021 ; Hotta, 2021 ; Mahasneh et al, 2021 ; Terra et al, 2021 ). In this study, genome sequencing revealed that the chromosome of the St. albidoflavus St-220 contained 21 conserved biosynthesis gene clusters (BGCs), of which 10 showed high similarities in structure with known BGCs encoding terpenes, non-ribosomal peptides, polyketides, siderophores, and ectoines, which had been proven to participate in the regulation of antimicrobial activities of Streptomyces strains ( van Bergeijk et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%